2014
DOI: 10.3748/wjg.v20.i39.14463
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of peripheral blood in colorectal cancer

Abstract: A novel gene expression profile was associated with CRC and can potentially be applied to blood-based detection assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
3
25
0
3
Order By: Relevance
“…The IL2RB gene encodes the interleukin(IL)-2 receptor-β which binds IL-2, a cytokine which plays a major role in T-cell differentiation and proliferation. Overexpression of lymphocyte IL2RB has been linked to risk of colorectal cancer in small clinical casecontrol studies and was shown to predict risk when combined with 6 additional genes 44,45 Given that obesity is accompanied by alterations in T-cell populations, inflammation and immune dysregulation 46 , our results provide a potential link between obesity, T-cell proliferative pathways and colorectal cancer development that warrants further study. The FGF18 gene, which encodes the fibroblast growth factor 18, has also been previously linked to colorectal tumorigenesis 47 .…”
Section: Discussionmentioning
confidence: 76%
“…The IL2RB gene encodes the interleukin(IL)-2 receptor-β which binds IL-2, a cytokine which plays a major role in T-cell differentiation and proliferation. Overexpression of lymphocyte IL2RB has been linked to risk of colorectal cancer in small clinical casecontrol studies and was shown to predict risk when combined with 6 additional genes 44,45 Given that obesity is accompanied by alterations in T-cell populations, inflammation and immune dysregulation 46 , our results provide a potential link between obesity, T-cell proliferative pathways and colorectal cancer development that warrants further study. The FGF18 gene, which encodes the fibroblast growth factor 18, has also been previously linked to colorectal tumorigenesis 47 .…”
Section: Discussionmentioning
confidence: 76%
“…Considering the above, we speculated that KRAS and MAP1 might be partly responsible for the confirmed associations between miR-132 and several cancers, such as colorectal cancer[ 8 ], glioma[ 10 ] and primary glioblastoma multiforme[ 58 ]. An earlier study by Chang, et al[ 59 ] has put forward the concept of applying gene expression profile of peripheral blood for the detection of colorectal cancer. Researchers interested can capitalize on methods mentioned[ 59 ] in combination with findings in the current research, namely, discovering whether the abovementioned hub genes, especially KRAS and MAP1, would be appropriate for blood-based detection assays in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by Chang, et al[ 59 ] has put forward the concept of applying gene expression profile of peripheral blood for the detection of colorectal cancer. Researchers interested can capitalize on methods mentioned[ 59 ] in combination with findings in the current research, namely, discovering whether the abovementioned hub genes, especially KRAS and MAP1, would be appropriate for blood-based detection assays in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were stored at 4°C until the peripheral mononuclear cell (PBMC) fraction was isolated, within 3 hours of collection. The PBMC fraction was used for further preparations according to Chang et al [49], including RNA extraction, reverse transcription, and real-time PCR analysis. All RNA and cDNA were stored at −80°C before analysis.…”
Section: Methodsmentioning
confidence: 99%